The Correlation Between High School Students Vocabulary Mastery And Writing Ability - Yuhariah, Feti; Sujarwati, Iis (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2023)
The aim of this study was to identify the relationship between students' writing abilities and their vocabulary knowledge. The method of this research is quantitative using two instruments: a 30-item multiple choice vocabulary test and a writing competency test using descriptive paragraphs. To analyze it, the Pearson Product Moment Correlation Formula is used to identify it. The research sample consisted of 36 middle schools students at 8 grade. The results of research regarding the relationship between vocabulary mastery and writing ability of middle schools students in science class show that there is a low relationship and show that the research hypothesis is proven. Based on this research, students should learn and use their vocabulary skills more to become a good writer.